Distribution of health problems at the general outpatients' clinic of the University of Hong Kong-Shenzhen Hospital: A cross-sectional study - Chen, Kai; Li, Zhuo; Liu, Ruihong; Zhu, Yanyan; Yan, Weihui; Pui, Ng Amy Pui; Chen, Zhiyuan (Frontiers in Public Health, 2022)
Objective: The study aimed to understand the distribution of health problems of a general practice clinic to provide guidance on how to develop primary care in Shenzhen, China. Study Design: This is a cross-sectional study. Methods: Patients’ sociodemographic data and diagnoses were recorded from the electronic medical record system of the University of Hong Kong-Shenzhen Hospital from Jan 2014 to Dec 2020 and coded using the International Classification of Primary Care-2. Descriptive statistics were used to describe the distribution of health problems. Results: A total of 368,167 health problems were recorded. Respiratory, digestive, musculoskeletal, general, and cardiovascular were the top five categories, which accounted for 67.71% of the total in this study. Acute upper respiratory tract infection (AURTI) was the most common health problem (6.67%). Chronic diseases, including hypertension and diabetes mellitus, accounted for about 7% of all health problems. The proportion of cardiovascular problems increased significantly with age (r=0.96, P＜0.05 ). The proportion of consultations for mental health problems was low in all age groups. Conclusions: The results represent an understanding of the common health problems of patients in Shenzhen city, which can provide a reference for preventing diseases and developing primary care.